Biologi Diachasmimmorpha longicaudata (Ashmead) (Hymenoptera : Braconidae) Parasitoid Larva Lalat Buah - Achmad Nasroh Kuswadi; Toto Himawan; Asep Ruhiyat Suherlan (Jurnal Perlindungan Tanaman Indonesia, 2007)
Biology of D. longicaudata, larval parasitoid of Bactrocera carambolae (Drew & Hancock) fruit fly was studied in the laboratory. Observation on ten pairs of adults, each pair confined in a laboratory cage, provided with third instar larvae of B. carambolae as their host, showed that the wasps mated 6-14 days after they emerged. They mated 2-5 times in their life time. Female wasps laid eggs until 18 days old, 1-6 eggs per day, with the average number of 58 eggs. Unmated female was able to lay viable eggs (parthenogenesis) that grew to male parasitoids (arrenotoky). The life cycle of D. longicaudata extended within 16 - 22 days. The eggs hatched 1-2 days after oviposition. Duration of the 1st, 2nd, 3rd and 4th instar larvae and the pupal stage were 1-2 days, 2-3 days, 3-4 days, 4-6 days and 4-5 days, respectively. First instar larvae was an active life stage, living in the third instar larvae of the host, while the following 2nd - 4th instar were inactive, living in the upae of the host. Adult parasitoid emerged from the puparium of host. In general, male wasp emerged 2-5 days earlier than the female.